Hydrogeochemical Characterization and Quality Assessment of Groundwater in Rumbai District, Pekanbaru: Implications for Sustainable Water Management - Ulfa Yusti; Yoseph, Boy; Hadi Hidayat; Septio, Ghenady (Journal of Geoscience, Engineering, Environment, and Technology, 2025)
Groundwater is a vital source of clean water, valued for its high quality, abundant reserves, accessibility, and cost-effectiveness. As a result, effective management is crucial to ensure compliance with relevant standards. However, rapid population growth and increasing human activities have raised the demand for groundwater, which, in turn, impacts its characteristics. These changes can include altered composition, imbalances in autotrophic nutrients, contamination by heavy metals, and seawater intrusion. The availability of reliable groundwater quality data is essential for sustainable development in Pekanbaru City. This research aims to assess the groundwater quality in Rumbai District, explore its hydrogeochemical characteristics, and analyze the distribution of bicarbonate based on physical and chemical parameters. This study is particularly significant as there has been no previous hydrogeochemical analysis of the peatland areas in this region. The research method involves a comprehensive analysis of groundwater conditions, focusing on both physical and chemical factors. The physical condition analysis includes the organoleptic assessment of smell to detect unusual odors, color inspection, and temperature. Total Dissolved Solids (TDS) and electrical conductivity (EC) levels are also measured, providing insight into the water's biological and chemical characteristics. The chemical condition analysis includes pH testing to assess the water's acidity or alkalinity, along with major ion analysis to evaluate the concentrations of cations like calcium, magnesium, sodium, and potassium, and anions such as chloride, sulfate, bicarbonate, and nitrate. For accurate results, proper sample collection using sterilized containers is critical, along with the use of replicates and instrument calibration. Data interpretation involves comparing the findings to established water quality standards, such as those from the World Health Organization (WHO), to assess the groundwater's suitability for consumption or other uses. Based on chemical properties standardized by the Ministry of Health, such as the pH value of water still meets the standard of 7.7, Na+ with an average of all stations is 20.49 Mg/l which still meets the standard, HCO3- with an average of all stations is 59.63 Mg/l l still meets the standard, CI- with the average of all stations is 19.75 Mg/l still meets the standard, SO42- with the average of all stations is 2.81 Mg/l still meets the standard. At ST-01, ST-02, ST-03, ST-04, ST-05, and ST-09, the groundwater meets the standards based on chemical analysis but does not meet the standards based on physical analysis. Meanwhile, ST-06, ST-07, ST-08, and ST-09 meet the required water quality standards based on both physical and chemical standards. Therefore, at ST-01, ST-02, ST-03, ST-04, ST-05, and ST-09, the groundwater is not suitable for use. So based on its chemical properties it still meets quality standards but this groundwater is influenced by the physical properties of groundwater which is not suitable for use at several stations. This study identifies four types of groundwater characteristics: the Na(K)-SO4 type, found at stations ST-01, ST-02, ST-04, ST-07, and ST-04; the Na(K)-HCO3 type, found at station ST-03; the Ca(Mg)-HCO3 type, found at stations ST-05, ST-06, and ST-08; and the Ca(Mg)-SO4 type, found at station ST-10.